The Main Character’s Conflict and Personality Analysis in “Encanto” Movie - Ni Wayan Rusminiati; Ni Wayan Suastini (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This research gave insight on Mirabel's conflicts and personality as depicted in the movie Encanto. In this study, the qualitative method was used to give more details and explained a simple summary of the conflicts and her personality as represented by the id, ego, and superego as the main human personality structures. It was investigated by using Kenney's (1966) conflicts theory as well as Freud's psychoanalysis theory (1896). Mirabel's internal conflict was illustrated when she tried to accept that she did not have any gift as she was unlucky girl. External conflicts included Mirabel versus Abuela, her mother, her sibling, nature and society. The conflicts led the researchers to three main personalities. The Id's personality is the humans have in order to get as much pleasure as possible. Mirabel's impulsive and anger behavior demonstrates the id. The ego's function is to find a realistic way to meet the demands. Mirabel’s ego was revealed when she ignored her heartbreak. The superego, which is idealistic, acts to restrain the will of the id and oblige the ego to act morally. Mirabel's super-ego was revealed when she requested an apology.